Multi-Omics Reveals Different Strategies in the Immune and Metabolic Systems of High-Yielding Strains of Laying Hens - Iqbal, Muhammad Arsalan; Reyer, Henry; Oster, Michael; Hadlich, Frieder; Trakooljul, Nares; Perdomo-Sabogal, Alvaro; Schmucker, Sonja; Stefanski, Volker; Roth, Christoph; Camarinha Silva, Amélia; Huber, Korinna; Sommerfeld, Vera; et al. (Frontiers in Genetics, 2022)
Lohmann Brown (LB) and Lohmann Selected Leghorn (LSL) are two commercially important laying hen strains due to their high egg production and excellent commercial suitability. The present study integrated multiple data sets along the genotype-phenotype map to better understand how the genetic background of the two strains influences their molecular pathways. In total, 71 individuals were analyzed (LB, n=36; LSL, n=35). Data sets include gut miRNA and mRNA transcriptome data, microbiota composition, immune cells, inositol phosphate metabolites, minerals, and hormones from different organs of the two hen strains. All complex data sets were pre-processed, normalized, and compatible with the mixOmics platform. The most discriminant features between two laying strains included, 20 miRNAs, 20 mRNAs, 16 immune cells, 10 microbes, 11 phenotypic traits, and 16 metabolites. The expression of specific miRNAs and the abundance of immune cell types were related to the enrichment of immune pathways in LSL strain. In contrast, more microbial taxa specific to the LB strain were identified, and the abundance of certain microbes strongly correlated with host gut transcripts enriched in immunological and metabolic pathways. Our findings indicate that both strains employ distinct inherent strategies to acquire and maintain their immune and metabolic systems under high-performance conditions. In addition, the study provides a new perspective into a view of the functional biodiversity that emerges during strain selection and contributes to the understanding of the role of host-gut interaction, including immune phenotype, microbiota, gut transcriptome and metabolome.